Association of Vitamin D Status and Clinical Outcome in Dogs with a Chronic Enteropathy. (26th August 2015) - Titmarsh, H.; Gow, A.G.; Kilpatrick, S.; Sinclair, J.; Hill, T.; Milne, E.; Philbey, A.; Berry, J.; Handel, I.; Mellanby, R.J.
Abstract : Background: Dogs with a chronic enteropathy (CE) have a lower vitamin D status, than do healthy dogs. Vitamin D status has been associated with a negative clinical outcome in humans with inflammatory bowel disease. Objectives: To examine the relationship between serum 25 hydroxyvitamin D (25(OH)D) concentrations at diagnosis and clinical outcome in dogs with a CE. Animals: Forty‐one dogs diagnosed with CE admitted to the Royal Dick School of Veterinary Studies, Hospital for Small Animals between 2007 and 2013. Methods: Retrospective review. Serum 25(OH)D concentrations were compared between dogs which were alive at follow up or had died because of non‐CE‐related reasons (survivors) and dogs which died or were euthanized due to their CE (non‐survivors). A binary logistic regression analysis was performed to determine significant predictors of death in dogs with CE. Results: Serum concentrations of 25(OH)D at the time a CE was diagnosed were significantly lower in nonsurvivors (n = 15) (median nonsurvivors 4.36 ng/mL, interquartile range 1.6–17.0 ng/mL), median survivors (n = 26) (24.9 ng/mL interquartile range 15.63–39.45 ng/mL, P < .001). Serum 25(OH)D concentration was a significant predictor of death in dogs with CE (odds ratio 1.08 [95% CI 1.02–1.18)]). Conclusions: Serum 25(OH)D concentrations at diagnosis are predictive of outcome in dogs with CE. The role of vitamin D in the initiation and outcome of chronic enteropathies in dogs is deserving of further study.